The hare and the tortoise - Robbins; Rita (Jamaica Mind to Mind, 2016)
The book uses simple language and colorful illustrations to convey the moral of the story: "Slow and steady wins the race." It's designed to teach young readers about the values of persistence, humility, and the importance of not underestimating others.